Discovering the relationship between natural resources, energy consumption, gross capital formation with economic growth: Can lower financial openness change the curse into blessing. (June 2021) - Yasmeen, Humaira; Tan, Qingmei; Zameer, Hashim; Vo, Xuan Vinh; Shahbaz, Muhammad
Abstract: The objective of this study is to discover the relationship between natural resources, gross capital formation, energy consumption and economic growth. In addition, the study also emphasizes on exploring whether financial openness can change the resource curse into a blessing. Using quarterly data from 1990Q1 to 2018Q4, the study used structural equation modeling technique for the empirical analysis. The conclusions of study indicated the negative relationship of natural resources with economic growth which confirms the existence of resource curse hypothesis. Although, renewable and non-renewable energy positively stimulate Pakistan's economic growth, but, the role of non-renewable energy toward economic growth is more strong compared with renewable energy. Financial openness also stimulates economic growth positively. However, the results for the influence of gross capital formation on economic growth were insignificant. The comprehensive assessment of the empirical examination of the role of financial openness in changing the resource curse into blessing indicated that financial openness doesn't have capability to change the resource curse into a blessing. The in depth analysis put-forward key guide lines for policy formation to efficiently utilize the natural resources in the country. Highlights: The study used structural equation modeling technique. Resource curse hypothesis has been verified in the context of Pakistan. Financial openness doesn't have capability to change the curse into a blessing. Energy consumption positively reinforce economic growth in Pakistan.